2016
DOI: 10.15517/rbt.v64i2.19100
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of habitat management on different feeding guilds of herbivorous insects in cacao agroforestry systems

Abstract: Human pressure on natural habitats increases the importance of agroforests for biodiversity conservation. The objective of this study was to evaluate the role of traditional cacao agroforests, known as “cabrucas,” on the conservation of the herbivorous insect community in compared with that of monodominant rubber agroforests. The insects were sampled in three habitats in southeastern Bahia, Brazil: native forests, cabrucas and rubber agroforests. In each habitat, 18 plots of 10 m<sup>2 </sup>were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…We collected beetles using combined flight Malaise/window traps ( Basset 1988 , Novais et al. 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…We collected beetles using combined flight Malaise/window traps ( Basset 1988 , Novais et al. 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…They attributed the differences to habitat specificity requirements of guild members [23]. Similarly, Novais et al (2016) found differences in the effect of canopy cover on different insect guilds, with percent canopy cover being positively associated with the richness of leaf-feeding insects, and negatively associated with the richness of sap-feeding insects, and with no significant relation to wood-boring insect richness [29]. These relationships, they concluded, depended in large part on the specific characteristics of the tropical agroforestry system they were studying and of the insect species present.…”
Section: Discussionmentioning
confidence: 99%
“…(3) predation risk on pests associated with certain predators and their abundance at different edges (including the "natural enemies hypothesis" prediction that higher plant diversity systems support more insect predators that more effectively control herbivore populations [29,33]), and (4) pest ecophysiological and life-history traits that are associated with ecological features and physical positions (i.e., forest layers) at forest edges [34].…”
Section: Discussionmentioning
confidence: 99%
“…We collected the insects using combined flight Malaise/window traps (Fig. 3B 50 , 66 ). With an exception, one trap per plot (9 total) holding two vial collectors with 70% ethanol were exposed for five days (120 h) in the canopy of the same tree during all sampling periods, at a height ranging from 4 to 7 m in the center of each plot.…”
Section: Methodsmentioning
confidence: 99%